Laparoscopic Repair of a Traumatic Intrapericardial Diaphragmatic Hernia - Kuy, SreyRam (Society of Laparoendoscopic Surgeons, 2014)
INTRODUCTION: Intrapericardial diaphragmatic hernia is a rare injury. We present a case of an intrapericardial diaphragmatic hernia from blunt trauma. In this report we will review the current literature and also describe the first report of a primary laparoscopic repair of the defect. CASE DESCRIPTION: A 38-year-old unrestrained male passenger had blunt chest and abdominal trauma from a motor vehicle collision. Two months later, on a computed tomography scan, he was found to have an intrapericardial diaphragmatic hernia. The defect was repaired primarily through a laparoscopic approach. DISCUSSION: Symptoms of intrapericardial diaphragmatic hernia are chest pain, upper abdominal pain, dysphagia, and dyspnea. Chest computed tomography is the most useful diagnostic test to define the defect. Even when the injury is diagnosed late, laparoscopy can be used for primary and patch repair.